Phosphorylated exogenous alpha-synuclein fibrils exacerbate pathology and induce neuronal dysfunction in mice - Mantia Karampetsou (8737815) (2017)
Approximately 90% of alpha-synuclein (α-Synuclein) deposited in Lewy bodies is phosphorylated at serine 129 suggesting that the accumulation of phosphorylated α-Synuclein is critical in the pathogenesis of Parkinson’s disease. However, in vivo experiments addressing the role of phosphorylated α-Synuclein in the progression of Parkinson’s disease have produced equivocal data. To clarify a role of Ser129 phosphorylation of α-Synuclein in pathology progression we performed stereotaxic injections targeting the mouse striatum with three fibrilar α-Synuclein types: wt-fibrils, phosphorylated S129 fibrils and, phosphorylation incompetent, S129A fibrils. Brain inoculation of all three fibrilar types caused seeding of the endogenous α-Synuclein. However, phosphorylated fibrils triggered the formation of more α-Synuclein inclusions in the Substantia Nigra pars compacta (SNpc), exacerbated pathology in the cortex and caused dopaminergic neuronal loss and fine motor impairment as early as 60 days post injection. Phosphorylated fibril injections also induced early changes in the innate immune response including alterations in macrophage recruitment and IL-10 release. Our study further shows that S129 phosphorylation facilitated α-Synuclein fibril uptake by neurons. Our results highlight the role of phosphorylated fibrilar α-Synuclein in pathology progression in vivo and suggest that targeting phosphorylated α-Synuclein assemblies might be important for delaying inclusion formation. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-017-15813-8